Sosialiasasi Dan Workshop Pembuatan Pupuk Organik Cair Dari Limbah Air Cucian Beras Di Desa Sangkub - Nizhamuddin AB; Nia Kurniasih Suryana; Hayrul Gunawan (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
The Socialization and Workshop on Liquid Organic Fertilizer Production from Rice Washing Water Waste in Sangkub Village aims to enhance the community's understanding of the benefits of liquid organic fertilizer. In this activity, participants are educated on the process of making fertilizer by utilizing rice washing water, which is often discarded in daily life. This initiative is expected to reduce farmers' dependence on chemical fertilizers, which are becoming increasingly expensive and hard to obtain. In addition to lowering agricultural production costs, the use of household waste such as rice washing water also has the potential to improve the quality and quantity of crop yields. The villagers are expected to apply the knowledge gained, significantly reducing the use of chemical fertilizers. The expected outcomes include increasing the community's knowledge and skills related to organic fertilizer production, effective utilization of waste, and improved agricultural yields. Success indicators include the number of participants, the extent to which the acquired knowledge is applied in practice, reduced use of chemical fertilizers, increased crop yields, and positive feedback from workshop participants. This activity is expected to provide a sustainable solution in supporting environmentally friendly agriculture in Sangkub Village.